2021
DOI: 10.1038/s41598-021-94438-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of a serum biomarker panel in distinguishing prostate cancer from benign prostate hyperplasia

Abstract: Prostate-specific antigen (PSA) screening for prostate cancer (PCa) is limited by the lack of specificity but is further complicated in the benign prostatic hyperplasia (BPH) population which also exhibit elevated PSA, representing a clear unmet need to distinguish BPH from PCa. Herein, we evaluated the utility of FLNA IP-MRM, age, and prostate volume to stratify men with BPH from those with PCa. Diagnostic performance of the biomarker panel was better than PSA alone in discriminating patients with negative bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…All men in the analysis cohort had a PSA in the range of 4-10 ng/mL and a negative digital rectal exam (DRE). Additional clinical characteristics of the study cohort are described in Table 1, also being previously published in [4]. In our previous study, we showed that logistic regression using a panel of FLNA, age, and prostate volume performed better than PSA in discriminating between men with PCa and men with BPH.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…All men in the analysis cohort had a PSA in the range of 4-10 ng/mL and a negative digital rectal exam (DRE). Additional clinical characteristics of the study cohort are described in Table 1, also being previously published in [4]. In our previous study, we showed that logistic regression using a panel of FLNA, age, and prostate volume performed better than PSA in discriminating between men with PCa and men with BPH.…”
Section: Methodsmentioning
confidence: 96%
“…We previously identified the level of a cleaved peptide of Filamin A (FLNA) in serum, when combined with prostate volume and age among men who all had elevated PSA levels between 4 and 10 ng/mL, that provided superior predictive performance compared to PSA in distinguishing between men with BPH and men with PCa [4]. The identified protein, FLNA, has been implicated for its role in PCa metastasis, which supports the biological plausibility that FLNA may be a serum biomarker for a PCa diagnosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the current prostate cancer screening program using PSA would not be desirable in a clinical setting, and it would only be recommended for men who express a specific interest in screening [ 132 ]. New tests are under evaluation, such as a recently developed biomarker panel combining filamin-A gene, age, and prostate volume which has a better performance than PSA alone, especially in men with benign hyperplasia [ 133 ].…”
Section: Clinical Applications Of Cancer Biomarkers: Examplesmentioning
confidence: 99%
“…Liquid biopsies utilizing body fluids such as blood, urine and saliva and analyzing biomaterials in circulation show promise for revolutionizing tumour profiling and monitoring practices. It contributes to understanding the signals determining threshold tumour development ( 6 ), highlights metastatic markers, and provides complementary information for treatment response ( 7 , 8 ). In addition to the biomarker potential, it begins to serve as a method for evaluating mechanisms behind therapy resistance ( 9 ).…”
Section: Mainmentioning
confidence: 99%